Draft Annual Plan 2012-13 Vol. II Union Territory of Lakshadweep - Planning Commission (Planning Commission, 2012)
INTRODUCTION OF THE SECTOR ; The Lakshadweep islands lies isolated towards the west cost of Indian peninsula and shipping is lifeline of Lakshadweep islands. The shipping services are the primary means of transportation of men and material between the islands and the mainland. Port Light Houses and Shipping sector augment the necessary infrastructure for Shipping Services such as procurement of passenger and cargo ships, inter-island ferries and crafts for ship to shore transport of men and material and other cargo handling equipments etc., Enhancement of jetties and berthing facilities, procurement and fabrication of mooring buoys etc. are highlighted in the current plan period. Construction of Eastern side Break waters, Establishment of Transport Hubs at Andrott and Port Hub for berthing inter island ferries at Kadmat and Agatti, Improvement of Port Work Shop with modern high-tech equipments, and a dedicated berth at mainland ports viz.
Union Territory of Lakshadweep